Creating Mini-Research Spaces in Problem Based Learning Curriculum using Abstraction - Karogal, Sinchan; Hegade, Prakash; Shettar, Ashok (Journal of Engineering Education Transformations, 2025)
When Problem-Based Learning and Computational Thinking are integrated as a teaching-learning pedagogy; they provide a comprehensive platform for both teachers and students, enhancing approaches to teaching and learning respectively. Abstraction being one of the aspects of computational thinking, can help computer science engineers to model a system design problem with social context and provide a mini-research space for further exploration. This study proposes a research question to explore on the lines of how computational thinking's abstraction can impact students’ ability to solve research-based problems in PBL scenarios. And also, how can it guide to build effective models. Abstraction is used a research intervention in the process. With Conceptual Change theory as a conceptual framework, this work compares the influence of abstraction on modeling problems in research space. Multi method is used as a research methodology for the study and selfselection is used as a sampling technique from the students who took a modeling course jointly offered by an industry Knit Space and KLE Technological University. Scenarios from arts and culture play a major impact in designing such problem scenarios. Library of Babel and Guernica were given as modeling problems which also have the social context and historical connection aspects. 50 student answer sheets were evaluated qualitatively and quantitatively for the study analysis. With appropriate descriptive measures, statistical methods like paired t-tests, student feedbacks, in-vivo coding and process coding, the collected data was analyzed for results and discussion. Along with statistical measures, this study discusses the themes generated from the study with an emphasis on research in curriculum design. The results positively align towards the conclusion that abstraction trigger points can aid in building research-based models.